Enrichment of loss-of-function and copy number variants in ventricular cardiomyopathy genes in 'lone' atrial fibrillation. Issue 6 (3rd March 2021) - Lazarte, Julieta; Laksman, Zachary W; Wang, Jian; Robinson, John F; Dron, Jacqueline S; Leach, Emma; Liew, Janet; McIntyre, Adam D; Skanes, Allan C; Gula, Lorne J; Leong-Sit, Peter; Cao, Henian; et al.
Abstract: Aims: Atrial fibrillation (AF) is a complex heritable disease whose genetic underpinnings remain largely unexplained, though recent work has suggested that the arrhythmia may develop secondary to an underlying atrial cardiomyopathy. We sought to evaluate for enrichment of loss-of-function (LOF) and copy number variants (CNVs) in genes implicated in ventricular cardiomyopathy in 'lone' AF. Methods and results: Whole-exome sequencing was performed in 255 early onset 'lone' AF cases, defined as arrhythmia onset prior to 60 years of age in the absence of known clinical risk factors. Subsequent evaluations were restricted to 195 cases of European genetic ancestry, as defined by principal component analysis, and focused on a pre-defined set of 43 genes previously implicated in ventricular cardiomyopathy. Bioinformatic analysis identified 6 LOF variants (3.1%), including 3 within the TTN gene, among cases in comparison with 4 of 503 (0.80%) controls [odds ratio: 3.96; 95% confidence interval (CI): 1.11–14.2; P = 0.033]. Further, two AF cases possessed a novel heterozygous 8521 base pair TTN deletion, confirmed with Sanger sequencing and breakpoint validation, which was absent from 4958 controls ( P = 0.0014). Subsequent cascade screening in two families revealed evidence of co-segregation of a LOF variant with 'lone' AF. Conclusion: 'Lone' AF cases are enriched in rare LOF variants from cardiomyopathy genes, findings primarily driven by TTN, and a novel TTN deletion, providing additional evidence to implicate atrial cardiomyopathy as an AF genetic sub-phenotype. Our results also highlight that AF may develop in the context of these variants in the absence of a discernable ventricular cardiomyopathy.